He4llo, cnmath16!
Solve the following system of equations using the elimination method
. .
My Answer:
Which gives you: . . . . . Good!
Substitute into [2]: .
Therefore: .
Solve the following system of equations using the elimination method
3x-9y=10 (1)
4x+y=7 (2)
I have completed this question, but I would like someone to look over it to make sure that I did the right thing, because it does not look like the right answer to me. Any help or comments would be appreciated.
Thanks!
My Answer:
3x-9y=10 (1)
4x+y=7 (2)
By elimination:
Take equation (2) and multiply by 9
Thus, (2) x 9 gives you 36x-9y = 63 (3)
Add equation 3 to 1
Which gives you 39x = 73 ... divide both sides by 39 and x= 73/39 or 1.87
Substitute x (1.87) into Equation #1 to find y:
3(73/39)-9y=10
..This is where I get confused.